(untitled) (South Asian Journal of Agriculture, 2019)
This study aimed to identify the socioeconomic and environmental challenges of the migrants who are migrated in Krishnonagar and Mohammadnagar areas of Khulna district. By using simple random sampling technique 348 (157 from Krishnanagar and 191 from Mohammadnagar) household heads were selected as the respondents. The length of living was considered to assess the effect of migration on the socioeconomic and environmental conditions of the respondents. Seven indicators (income, occupation, education, class, family status, poverty situation and health) were considered to assess the socioeconomic conditions of the respondents. The regression analysis supports that the length of migration has its effect on income (71%), poverty situation (66%) and class position (64%) of the respondents. That means the socioeconomic conditions of the people living in the study areas for long time is better than those of new migrants. In this study environmental issues include water and air quality, housing conditions, waste disposal systems and related hazards affected by the respondents as the migrants. The respondents were migrated from different areas of Bangladesh mainly due to natural disaster and crop cultivation related vulnerability. Among the total respondents 87.4 percent of the household heads are male and 12.6 percent are female. The present study shows that nearly half of the respondents (47.7%) in the study area were found to be involved in seasonal work. The average monthly household income in the study areas was 5892 BDT and 55.2 percent respondents were absolutely poor. About 17 percent respondents claimed for the ownership of the house but 57.87 percent were living in rented house. Among the environmental challenges waterlogging and problem of solid waste disposal were severe. In this regard some useful points of recommendations for effective urban management and rural development activities are suggested. South Asian J. Agric., 7(1&2): 6-14